Avaliação clínica da adaptação marginal e interna de coroas cerâmicas pela técnica da réplica em silicone - Serpa, Gabriela Andrade (2021)
The objective of this study was to clinically evaluate the marginal and internal fit of veneered ceramic crowns and compare to the adaptation obtained on the plaster die of the working cast. Twenty-five molar layered crowns were made of zirconia (IPS e.max ZirCAD) and lithium disilicate glass-ceramic (IPS e.max Press). The marginal and internal fit, both clinically (on the preparation in the mouth) and on the plaster cast of the working cast, were evaluated using the silicone replica technique. The replicas were cut into two segments, resulting in four fragments, and digitized in high resolution. Four points were evaluated: margin (MG), axial wall (AW), axio-occlusal angle (AO) and occlusal area (CO). Data were analyzed by paired and unpaired Student's t-test (α = 5%). Considering each of the evaluated points, clinically (on the preparation in the mouth), there was no significant difference when comparing the zirconia and glassceramic crowns [MG (p = 0.212), AW (p = 0.918), AO (p = 0.765), CO (p = 0.897)]. Comparing the marginal and internal fit on die and clinically, for glass-ceramic crowns, there was no significant difference [MG (p = 0.975), AW (p = 0.406), AO (p = 0.493), CO (p = 0.844)]. For zirconia, there was no significant difference in 3 of the 4 points [MG (p = 0.727), AW (p = 0.209), CO (p = 0.212)], except for the AO point (p = 0.017, in mouth 151.5 ±57.1 μm and on the die 191.8±47.9 μm). It can be concluded that, clinically, the marginal and internal fit of lithium disilicate glass-ceramic and zirconia crowns was similar in all assessed points. On the other hand, when comparing the marginal and internal fit of the crowns on plaster die of the working model and clinically, in the mouth, the zirconia crowns presented greater clinical misfit at the axioocclusal angle.